The Suitability Analysis of the Occupational Safety and Health Management System (OSHMS) Application at the Budhi Asih Jakarta Hospital - Marsanda Chory Prames Wary; Tatan Sukwika; PS. Dyah Prinajati (Journal of Applied Management Research, 2023)
Budhi Asih Hospital is one of the regional general hospitals (RSUD) in Jakarta. Accidents are often the result of negligence while working by medical personnel. Applying an occupational safety and health management system (OSHMS) according to standards can provide OSH guarantees for medical staff. The study aimed to find the suitability of the implementation of OSHMS with Government Regulation Number 50 of 2012 and the factors that influence the implementation of OSHMS in Budhi Asih Hospital. The research method uses a descriptive qualitative approach. Data collection through checklist interviews on PP No. Indicators. 50 of 2012, interviews, observations, and documentation. The results showed that RSUD Budhi Asih implemented OSHMS according to Government Regulation No. 50 of 2012, namely 87%. It means that the suitability level is satisfactory. At the same time, some elements still need to be implemented, and factors that influence the implementation of OSHMS, namely elements of commitment to awareness of human resources, consistency of socialization from the HOSH team, infrastructure, and a budget that still needs to be improved. This study concludes that most Budhi Asih Hospitals have implemented OSHMS by Government Regulation 50 of 2012 in the excellent category. This research suggests that the management of the East Jakarta Budhi Asih Hospital evaluates elements that still need to be improved, such as socializing the application of OSH culture and reporting within the Budhi Asih Hospital environment.